Professional Development of Teachers, Competencies, Educational Facilities and Infrastructure on Teacher Performance and Learning Achievement of High School Students in Makassar City - Ybnu Taufan, Muhammad (Manunggal Halim Jaya, 2022)
This study aims to analyze teacher professional development, competence, educational facilities, and infrastructure that affect teacher performance and high school student learning achievement. The population in this study was all teachers from five public high schools and five private high schools, with 183 teachers as samples. The analytical model used in this study is a structural equation model (SEM) using the AMOS program. The results showed that teacher professional development has no significant effect on the performance. Competence, educational facilities, infrastructure, and teacher professional development, have a positive and significant effect on teachers' performance. Competence has no significant impact on the performance of teachers. Educational facilities and infrastructure have a positive and significant effect on student learning achievement. Teacher performance has a positive and significant effect on students' learning achievement. Teacher professional development has a positive and significant effect on the learning achievements of high school students through teacher performance. Competence has a positive and significant effect on the learning achievement of high school students through teacher performance. Educational facilities and infrastructure have a positive and significant effect on the learning achievements of high school students through teacher performance.